Narratives of resilience: Applying Emmy Werner’s framework to Jeannette Walls' The Glass Castle - Ikrimah, Zahra; Farida, Hana; Wajiran, Wajiran (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This article employs Emmy Werner’s resilience theory to analyze Jeannette Walls’ memoir, The Glass Castle (2005). It examines how the dynamic interplay of risk and protective factors shaped Walls’ developmental trajectory, enabling her to overcome profound childhood adversity. While prior scholarship has often focused on trauma, dysfunctional family dynamics, or feminist readings of the text, this study offers a focused literary-psychological analysis through the lens of resilience. Werner’s framework, derived from longitudinal studies of at-risk children, provides a robust model for understanding mechanisms of positive adaptation despite significant hardship. Utilizing a qualitative descriptive methodology, the analysis identifies salient risk factors in Walls’ childhood, including severe poverty, parental neglect and instability, and her parents’ alcoholism. Concurrently, it delineates key protective factors that fostered resilience: her innate problem-solving skills, a strong sibling alliance, external support from educators, and her internal determination. The findings demonstrate that Walls’ resilience was forged within a context of persistent risks but was catalyzed by specific protective elements that facilitated adaptive coping, academic success, and ultimate socio-economic mobility. By applying Werner’s psychological framework to a literary memoir, this study bridges disciplinary boundaries, illustrating how personal narrative can empirically model the constructs of developmental psychology. It argues that The Glass Castle functions not merely as a story of trauma, but fundamentally as a narrative of hope and human capacity for resilience.